Slaughter analysis, incidence of myopathy and breast muscle characteristics of broiler chickens fed crude fibre concentrate feeds - Urban, Jakub; Bień, Damian; Matuszewski, Arkadiusz; Ciborowska, Patrycja; Zalewska, Anna; Pietrzak, Dorota; Chmiel, Marta; Jaroszek, Adriana; Graham, Lucas Elzie; Michalczuk, Monika (Journal of veterinary research, 2025)
INTRODUCTION: This study investigated the impact of adding crude fibre concentrate (CFC) to broiler chicken diets on slaughter results and breast muscle quality. MATERIAL AND METHODS: A total of 990 male Ross 308 chicks were divided into control (C), experimental 1 (A1) and experimental 2 (A2) groups. Experimental diets contained CFC at different levels: A1 had 0.4% in the starter diet, 0.8% in the first grower diet, 0.8% in the second grower diet and 0.2% in the finisher diet, and A2 had 0.6%, 1.0%, 1.2% and 0.4% in the same diets. On day 42, 20 birds per group were slaughtered and dissected. Breast muscles were weighed and visually assessed for myopathic defects (white striping, wooden breast and "spaghetti" meat). The tissue was also analysed for residual myopathy incidence and associated physicochemical properties, namely drip loss, shear force, pH, water holding capacity, collagen content, colour parameters and basal chemical composition. RESULTS: Consumption of the CFC additive statistically significantly reduced (P-value ≤ 0.05) white striping defects and increased final live weight by 2.1% for birds in group A1 and by 3.3% in group A2. Group A1 carcasses also weighed 6.7% more and group A2 carcasses 4.1% more. Additionally, A1 carcasses yielded 1.5% more and A2 carcasses 0.8% more leg muscle, also statistically significantly greater yields than C carcasses (P-value ≤ 0.05). The slaughter yield of birds in group A1 was 3.3% higher (P-value ≤ 0.001) than that of birds in group C. The use of the CFC additive in the diets of both experimental groups had no adverse effect on the other analysed parameters. CONCLUSION: Crude fibre concentrate addition to the complete feed mixture is recommended for improving the results of the slaughter analysis and the visual quality of meat.
Keywords: crude fibre; chicken broiler; breast muscle quality; slaughter performance